2012
DOI: 10.1155/2012/391546
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mechanisms to Initiate Translation in Eukaryotic mRNAs

Abstract: The composition of the cellular proteome is under the control of multiple processes, one of the most important being translation initiation. The majority of eukaryotic cellular mRNAs initiates translation by the cap-dependent or scanning mode of translation initiation, a mechanism that depends on the recognition of the m7G(5)ppp(5)N, known as the cap. However, mRNAs encoding proteins required for cell survival under stress bypass conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 156 publications
(155 reference statements)
1
43
0
1
Order By: Relevance
“…Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012). Although the presence of an IRES element is a common feature of all picornavirus RNAs, some differences affecting the organization of the 5 UTR, described below, are specific of each genus.…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012). Although the presence of an IRES element is a common feature of all picornavirus RNAs, some differences affecting the organization of the 5 UTR, described below, are specific of each genus.…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…Many animal RNA viruses conduct cap-independent translation by attracting ribosomes to extensive, highly structured cis-acting RNA elements known as internal ribosome entry sites (IRES). Viral IRES are located near , or span the initiation codon and recruit required initiation factors or ribosomal subunits directly (Hertz and Thompson, 2011; Martinez-Salas et al, 2012). Plant viruses can also contain 5’ IRES, which for Tobacco etch potyvirus recruits eIF4G within the eIF4F complex as well as the 40S ribosomal subunit for initiation of polyprotein translation (Basso et al, 1994; Gallie, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although most cellular mRNAs initiate translation by a cap-dependent mechanism, alternative mechanisms are operative when cap-dependent translation is compromised, including IRES-dependent translation initiation. 3,4,28 Most known IRES elements are located in the 5′ UTR of mRNAs upstream of the initiator codon, but some exceptions exist. [29][30][31][32] Furthermore, although cellular IRES elements described so far lack conserved structural features, 3,4 RNA structure plays a fundamental role in viral IRES-dependent translation initiation.…”
Section: Discussionmentioning
confidence: 99%